Promotion and animal welfare - Vetter, Szilvia (Animal welfare, Ethology and Housing Systems (AWETH), 2014)
Society uses animals for many ways to support our own interests and well-being. In recent years though, animal welfare has become a prominent corporate social responsibility (CSR) issue for companies in many countries, and they have a rational reason for that. Recent statistics and surveys show a clear tendency: consumers do care about farm animal welfare, it is in connection with brand reputation. Improving animal welfare is likely to improve public perception and image. Concern for animals is evident now throughout many societies. Most developed countries have by now introduced animal welfare regulations. There are certain fields of economical activities, where the question of animal welfare is in focus, for example in companies working in the food industry. Although food safety was the primary consumer concern, animal welfare is increasing in significance. For example, 74% of the European citizens think, that buying animal-friendly products could have a positive impact on the protection of farm animals. Despite all these, consumers don’t necessarily change their eating habits as a result. One of the obvious explanations could be, that due to the lack of information consumers cannot distinguish between animal-friendly and non-animal-friendly products. That means, if a company is able to communicate its animal-friendly technologies effectively and can provide enough information for the consumer, it can gain an advantage in the market. To achieve this goal, the company should use all tools of marketing communication: advertising, social media, direct mail or e-mail campaigns, optionally catalogs, shows and seminars. An appropriate mix of all these with high quality implementation and a strong, clear message can be beneficial both for the company and the consumer. It’s highly advisable to examine some outstanding examples for a successful animal-friendly marketing mix from around the world.